Proteus Syndrome in the minimal form: atypical case report - Cunico, Caroline; Silva, João Luis Vieira da; Mugnol, Leonardo; Fedato, Rosangela Alquieri; Cunha, Luiz Antonio Munhoz da (Journal of the Foot & Ankle, 2020)
This is the case report involving a 14-year-old male patient with Proteus syndrome. In an outpatient consultation, the patient complained of pain in the right foot on exertion. On physical examination, the findings were gigantism observed through lateral growth of the right foot, hemangioma on the back, and lipomas on the forearm. Clinical follow-up and orthotic measures were introduced after clinical and baropodometric analyses, achieving total relief of complaints. The minimal form of Proteus syndrome is rare and its diagnosis is hard. Its diverse manifestations constitute an obstacle to a systematic approach, hence its treatment must be individualized for each particular patient. Level of Evidence V; Therapeutic Study; Expert Opinion.